Larval Settlement on Marine Surfaces The Role of Physico-Chemical Interactions - Cima, Francesca (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Selected studies focussing on various aspects of the evaluation of marine larval settlement on both natural and artificial surfaces, including those on pro-fouling and anti-fouling systems, have been collected for advancing our understanding of larvae-surface interactions. Biofouling is a large problem worldwide since it often causes severe damage to submerged structures, but it also leads to the formation of a well-structured community on natural hard substrata characterised by ecological succession and can be considered an important source of biodiversity. Therefore, the influence of a substratum's physico-chemical interactions on the settlement of various organisms of the macrofouling community represents an essential factor in choosing an appropriate artificial surface for application in a variety of coastal marine ecosystems. This reprint will certainly be greatly beneficial with respect to addressing the challenges of future innovative eco-engineering designs, yielding the best solutions for industrial biofouling protection and coastal ecosystem preservation.